Bacillus Probiotics as Alternatives to In-feed Antibiotics and Its Influence on Growth, Serum Chemistry, Antioxidant Status, Intestinal Histomorphology, and Lesion Scores in Disease-Challenged Broiler Chickens - Ogbuewu, Ifeanyi Princewill; Mabelebele, Monnye; Sebola, Nthabiseng Amenda; Mbajiorgu, Christian (Frontiers in Veterinary Science, 2022)
In commercial poultry production, chickens are reared under intensive conditions, which allow infections to spread quickly. Antibiotic growth promoters (AGPs) are used in livestock and poultry production to control diseases as well as to maintain health and productivity. However, restrictions on the use of AGPs in livestock production due to growing concerns of antimicrobial resistance (AMR), together with antibiotic residues in meat and eggs has prompted poultry researchers and feed producers to look for viable alternatives. Probiotics, specifically from the genus Bacillus have proven to be effective due to their spore-forming capabilities. In commercial poultry production, chickens are reared under intensive conditions, which allow infections to spread quickly. Antibiotic growth promoters (AGPs) are used in livestock and poultry production to control diseases as well as to maintain health and productivity. However, the restriction on the use of AGPs in livestock production due to growing concerns of antimicrobial resistance, together with regulatory pressure and consumer demands for antibiotic-free foods has prompted poultry researchers and feed producers to look for viable alternatives. Probiotics, specifically from the genus Bacillus have proven to be effective due to their spore-forming capabilities. Furthermore, their ability to withstand heat during feed processing and be stored for a long time without losing viability as well as their potential to function in the acidic medium of the chicken gut, provide them with several advantages over conventional probiotics. This review discusses the mechanisms by which Bacillus improves growth performance in disease-challenged broiler chickens. This review discusses the mechanisms by which Bacillus improves growth performance in disease-challenged broiler chickens. Antioxidant and antimicrobial properties of Bacillus probiotics were also discussed. The effect of Bacillus probiotic on the blood and intestinal histomorphological indices of disease-challenged broiler chickens was also explained. It is concluded that Bacillus probiotic improves growth and productivity of disease-challenged broiler chickens and can be a good alternative to AGPs; however, more studies are required to maximize broiler productivity and achieve the ultimate goal of stopping the usage of AGP in broiler chickens production.